Mitochondrial genomes of eight Scelimeninae species (Orthoptera) and their phylogenetic implications within Tetrigoidea - Li, Ran (PeerJ, 2021)
Scelimeninae is a key member of the pygmy grasshopper community, and an important ecological indicator. No mitochondrial genomes of Scelimeninae have been reported to date, and the monophyly of Scelimeninae and its phylogenetic relationship within Tetrigidae is still unclear. We sequenced and analyzed eight nearly complete mitochondrial genomes representing eight genera of Scelimeninae. These mitogenomes ranged in size from 13,112 to 16,380 bp and the order of tRNA genes between COII and ATP8 was reversed compared with the ancestral order of insects. The protein-coding genes (PCGs) of tetrigid species mainly with the typical ATN codons and most terminated with complete (TAA or TAG) stop codons. Analyses of pairwise genetic distances showed that ATP8 was the least conserved gene within Tetrigidae, while COI was the most conserved. The longest intergenic spacer (IGS) region in the mitogenomes was always found between tRNA(Ser(UCN)) and ND1. Additionally, tandem repeat units were identified in the longest IGS of three mitogenomes. Maximum likelihood (ML) and Bayesian Inference (BI) analyses based on the two datasets supported the monophyly of Tetriginae. Scelimeninae was classified as a non-monophyletic subfamily.